Synchronous carrier-based pulse width modulation switching method for vienna rectifier - Park, Jin Hyuk; Yang, Song Hee; Lee, Kyo Beum (Journal of Power Electronics, 2018)
This paper proposes a synchronous switching technique for a Vienna rectifier that uses carrier-based pulse width modulation (CB-PWM). A three-phase Vienna rectifier, similar to a three-level T-type converter with three back-to-back switches, is used as a PWM rectifier. Conventional CB-PWM requires six independent gate signals to operate back-to-back switches. When internal switches are operated synchronously, only three independent gate signals are required, which simplifies the construction of gate driver circuits. However, with this method, total harmonic distortion of the input current is higher than that with conventional CB-PWM switching. A reactive current injection technique is proposed to improve current distortion. The performance of the proposed synchronous switching method and the effectiveness of the reactive current injection technique are verified using simulations and experiments performed with a set of Vienna rectifiers rated at 5 kW.
Keywords: Current distortion; Gate driver circuit; Internal switches; Reactive currents; Synchronous switching; Total harmonic distortion (THD); Vienna rectifiers; Zero crossing points; Current distortion near the zero-crossing point; Reactive current injection method; Synchronous switching method; Vienna rectifier